BLUE AMAZON: THINKING ABOUT THE DEFENCE OF THE MARITIME TERRITORY - Wiesebron, Marianne (AUSTRAL: Brazilian Journal of Strategy & International Relations, 2022)
The Brazilian Navy launched the concept Amazônia Azul to draw attention to the resources in the Ocean, and their importance for the Brazilian economy. This also implies thinking about the defence of these national resources and about the investments needed for the Navy to have the capacity to protect the maritime territory under Brazilian jurisdiction.